Pemilihan Angkutan Mudik Lebaran Menggunakan Metode Analytic Hierarchy Process - Narti Narti; Ahmad Yani; Adika Dharma Setiyadi (LPPM Universitas Bina Sarana Informatika, 2020)
Transportation or transportation from humans or goods from one place to another using vehicles that are driven by humans or machines. In the selection of public transportation back and forth it is sometimes difficult to determine suitable transportation for use in this case the community can support the decision support system method, one of which is the Hierarchy Analysis Process (AHP). AHP itself is a method that breaks up complex, unstructured places, and organizes parts or variables into a hierarchical form. In determining decisions using the AHP method the community can determine which transportation is more important with the value that must be determined. In this study four criteria were used namely price, service, quality and purpose of travel. In this study four alternatives were also taken, including bus, plane, fire train and sea boat. The existence of this research is expected to be able to help and facilitate the community in choosing the right vehicles for going home at Lebaran.